Education in Medical Informatics in the Federal Republic of Germany)) - Koeppe, P. (Methods of Information in Medicine, 1977)
The paper deals with the present situation of education at the academic level in Medical Informatics (or Medical Information Science, Electronic Data Processing applied to medicine and the health care service etc.) in the Federal Republic of Germany.Following some introductory remarks about definitions, tasks, and prospects, the different types of education and their availability at certain universities are described. The current capacity is about 100 graduations per year.It is estimated by the author that in future the average number of positions to be occupied by medical computer scientists will be in the order of 50 per year for the Federal Republic of Germany including Berlin (West).It is, therefore, concluded that the present capacity in regard to graduations is sufficient. More emphasis should be laid on developing and organizing curricula for further qualification as well as refresher courses for those already engaged in the field of medical informatics.
Keywords: Education; Medical Information Science; Forecast of Requirements; Post-graduate Study